Algoritma Support Vector Machine Untuk Analisis Sentimen Masyarakat Indonesia Terhadap Pandemi Virus Corona Di Media Sosial - Mhd. Furqan; Mhd. Ikhsan; Rafizah Aini (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The corona virus pandemic refers to the spread of coronavirus disease 2019 or what is known as coronavirus disease 2019 in various parts of the world. This outbreak is a change from a new type of coronavirus called SARS-CoV-2. The issue of this pandemic has become a hot topic of discussion, including on social media. The most frequently used platform among the public is Twitter. On social media, the corona virus pandemic has always been a topic of conversation that is often discussed, causing controversy. Controversy occurs because every day the opinions on social media Twitter regarding the corona virus pandemic are always increasing so that, when people read news on social media about the pandemic, it raises concerns because people's opinions are different. From this problem the author will create a system that analyzes opinions from Twitter social media to get opinion sentiment about what is happening in the community regarding the problem of the corona virus pandemic. This study uses the SVM method which is fast and effective for text classification. The results of this study will classify positive, negative and neutral sentences. The accuracy obtained from the model with the SVM algorithm is 98%. Testing is done by calculating precision, recall, F-measure..